TYPE 2 DIABETES MELLITUS: PATHOPHYSIOLOGY, CLINICAL PROGRESSION AND MODERN MANAGEMENT (Journal of Universal Science Research, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic progressive metabolic disorder characterized by insulin resistance and pancreatic beta-cell dysfunction. It represents one of the most significant global health burdens of the 21st century. This paper examines the epidemiology, pathophysiology, clinical manifestations, complications, diagnostic criteria, and contemporary treatment approaches of T2DM. The study is structured according to the IMRAD format and integrates current evidence-based guidelines.